Diet and Hygiene as Risk Factors in Dental Caries - Case Report - Ruxandra Margarit; O.C. Andrei; C. Daguci; C. Farcasiu (Romanian Society of Oral Rehabilitation, 2011)
Tooth decay is a disease with multifactorial etiology: diet, oral hygiene, dental tissue susceptibility, cariogenic bacteria. In developed countries, dental decay is more prevalent due to increasing consumption of carbohydrates. Caries occur because of demineralization of enamel and dentine by organic acids formed by bacteria in dental plaque through the anaerobic metabolism of dietary sugars. Numerous studies have shown that sugar is the most important factor in dental caries development and its correlation with poor hygiene leads to irreversible damage of hard dental structures. This paper presents the case of a young male patient, 23 years old, with a very high decay risk due to excessive consumption of carbohydrates, in the absence of proper oral hygiene. The patient failed to significantly change his diet and hygiene for a period of six months. All the teeth were affected on large surfaces. Since the lesions included almost the entire coronary volume reaching the coronary pulp chamber, the teeth could no longer be restored by simple fillings. In order to complete oral rehabilitation and to prevent early loss of teeth relative to the patient's age, we covered all the teeth with porcelain-fused-to-metal crowns. Caries risk assessment is an important component of dental management. It should be take into account the number and extension of present caries, patient‟s diet and hygiene and the saliva characteristics. Lack of hygiene combined with a diet based mainly on carbohydrates leads to an increased number of caries. Caries complications affect the patient both in terms of chewing and psychological function. For patients who fail to make changes in diet and in the oral hygiene‟s habits, early loss of teeth can be prevented by covering those teeth with crowns.